Circulating Levels of CILP2 Are Elevated in Coronary Heart Disease and Associated with Atherosclerosis - Hu, Wenjing (Oxid Med Cell Longev, 2020)
METHODS AND RESULTS: Circulating CILP2 levels (measured by ELISA) were compared to various insulin resistance- and atherosclerosis-related parameters in normal subjects and newly diagnosed CHD patients. THP-1 cells were cultured and treated with indicated stimulators. Western blots and RT-PCR were performed to examine protein and mRNA expressions. The results showed that there were significantly higher circulating CILP2 levels in CHD patients relative to healthy controls. Circulating CILP2 correlated positively with waist-hip ratio (WHR), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), HbA1c, homeostasis model assessment of insulin resistance (HOMA-IR), and Gensini scores. In an in vitro study, we found that CILP2 increased oxidatively modified LDL-stimulated lipid accumulation in THP-1 macrophages via the upregulation of CD36 expression. Inhibition of PPARγ signaling eliminated the CILP2 regulation of CD36 expression in THP-1 macrophages. CILP2 positively regulated CD36 transcription through PPARγ-mediated action on two peroxisome-proliferator-responsive elements (PPREs) binding sites of CD36 promoter, PPRE-G, and PPRE-J. CONCLUSIONS: Our findings have uncovered a novel role for CILP2 in lipid uptake and foam cell formation. This role is mediated by CD36 through the activation of PPARγ pathway.